Trends in Expert System Development: A Practicum Content Analysis in Vocational Education for Over Grow Pandemic Learning Problems - Ana, Ana (Indonesian Journal of Science and Technology, 2020)
The impact of the COVID-19 has emerged as a varied issue, ranging from the economy, society's social order, and education, especially when social and physical distancing have been introduced in various areas of community activities as one of the prevention. It has also affected the tertiary education institution where learning activities should be conducted from and at home, forcing the higher education communities to shift learning from conventional learning to online learning. Needless to say, learning that does not require practicum is easier compared to learning that needs it. Consequently, it is a new task for lecturers to ensure the meaningful practicum learning implementation is conducted as it should be. Therefore, the creation of expert systems for practicum learning in vocational education is urgently required in online learning. The aim of this literature review was to examine the development of an expert system used at practicum learning in tertiary institutions and how the design of learning systems could be integrated into vocational education in facing the COVID-19 pandemic. The method used was the literature study, through research stages starting from the finding and selection of articles and journals with relevant topics, and then analysing the data. The findings of this study was to identify the development of an expert program in an attempt to promote practicum learning using e-learning in the midst of the COVID-19 pandemic outbreak.